Prediction Models for Complete Resection in Secondary Cytoreductive Surgery of Patients With Recurrent Ovarian Cancer - Jiang, Caixia; Li, Zhengyu (Frontiers in Oncology, 2021)
Most advanced epithelial ovarian cancer develop recurrent disease despite maximal surgical cytoreduction and adjuvant platinum-based chemotherapy. And treatment of secondary cytoreductive surgery (SCS) combined with chemotherapy or chemotherapy alone for patients with platinum-sensitive recurrent ovarian cancer (ROC) is currently under heated discussion. Encouragingly, results of the AGO DESKTOP III study and SOC1/SGOG-OV2 trial were recently published, which showed a striking advantage in the terms of overall survival (OS) and progression-free survival (PFS) of ROC patients undergoing SCS compared to chemotherapy alone; moreover, a benefit of SCS exclusively for patients with complete gross resection (CGR) was particularly highlighted. CGR is considered the ultimate goal of SCS on condition that balance between maximal survival gain and minimal operative morbidity is maintained. Several models have been proposed to predict the rate of CGR such as the MSK criteria, AGO Score and Tian model over the last 15 years. This summary is mainly about several previously published prediction models for CGR in SCS of ROC patients, and discuss the effectiveness and limitations of these prediction models.